DOES ROBUSTA COFFEE COMMONITY NEED A FUTURES CONTRACT? - Paramu, Hadi; Sumardi, Nurul Afifah; Puspitasari, Novi (Universitas Jember, 2024)
ABSTRACTThe coffee commodity is faced with a major problem, namely significant world price fluctuations which create financial risks in international trade in coffee commodities. Coffee exporters must manage risks arising from fluctuations in the price of robusta coffee in the commodity market. On the commodity exchange, futures contracts are available on coffee commodities which can be used to hedge risks. The aim of this research is to analyze whether robusta coffee exporters should implement hedging strategies or not. The analysis method used is a Monte Carlo simulation approach. The simulation was carried out to estimate commodity prices at the maturity date of the futures contract based on 960 historical data on daily commodity prices. Based on 500 experiments (simulations) on spot prices, the simulation results show that hedging using futures contracts tends to be better not done. Coffee commodity transactions on the physical market are considered to generate better income for exporters.Keywords: Coffee; Futures Contract;Hedging; Simulation ABSTRAKKomoditas kopi dihadapkan permasalahan utama, yaitu fluktuasi harga dunia yang signifikan yang menimbulkan risiko finansial dalam perdagangan internasional komoditas kopi. Eksportir kopi harus mengelola risiko yang timbul karena fluktuasi harga kopi robusta di pasar komoditas. Pada bursa komoditas, tersedia kontrak futures pada komoditas kopi yang dapat digunakan untuk lindung nilai (hedging) atas risiko. Tujuan dari penelitian ini adalah untuk menganalisis apakah eksportir kopi robusta sebaiknya menerapkan strategi hedging atau tidak. Metode analisis data yang digunakan yaitu menggunakan pendekatan simulasi Monte Carlo. Simulasi dilakukan untuk mengestimasi harga komoditas pada masa jatuh tempo kontrak futures berdasarkan 960 data historis harga komoditas harian. Berdasarkan 500 kali percobaan (simulasi) pada harga spot, hasil simulasi menunjukkan bahwa hedging menggunakan kontrak futures cenderung lebih baik tidak dilakukan. Transaksi komoditas kopi pada pasar fisik dinilai menghasilkan pendapatan yang lebih baik untuk eksportir.Kata Kunci: Hedging; Kontrak Futures; Kopi; Simulasi